The economics of Soviet oil and gas - Campbell, Robert Wellington; Resources for the Future (Baltimore, Published for Resources for the Future by the Johns Hopkins Press, 1968)
Beginning with the development of the Soviet energy economy, the author discussed in detail aspects of the industry as its organization and administration, drilling, production transportation, gas etc
Include bibliographical references and index
kjo 15/01/2019
Loans
Keywords: Petroleum industry and trade; Soviet Union